Design and implementation of an automatic cleaning machine for evaporation tanks - WANG Mingjuan; LIANG Fangui; JIANG Yu (Shipin yu jixie)
ObjectiveIn order to solve the problems of low manual cleaning efficiency, poor cleaning quality, and the risk of burns.MethodsAn automatic cleaning machine for boiling sugar evaporation tanks which could be positioned and walked above the heating tube array had been developed. This cleaning machine was equipped with a spray head that could spray high-pressure water flow, and the spray head could extend to different depths inside the pipe to complete comprehensive cleaning of the inner walls of each heating pipe in the tank room. Based on the structure and workflow of the cleaning machine, a heating tube center detection and path planning program, hardware control system, and a single and double cleaning mechanism cleaning machine prototype were designed according to the requirements of different specifications of evaporation tanks.ResultsThe efficiency of a single cleaning machine was higher than that of manual cleaning. When the heating pipes were evenly distributed, the efficiency of a dual flushing mechanism prototype could reach twice that of a single flushing mechanism prototype.ConclusionThe cleaning machine has high work efficiency, good cleaning effect, safe and stable operation, and meets the requirements of automatic cleaning operations.